Cover Image, Volume 25, Issue 4. (April 2017) - Lu, Guilin; Zheng, Fei; Wang, Jianqiang; Shen, Wenzhong
Abstract : The cover image, by Guilin Lu et al., is based on the Original Article Thin Al2 O3 passivated boron emitter of n ‐ type bifacial c ‐ Si solar cells with industrial process, DOI:10.1002/pip.2859 .